2021
DOI: 10.1007/s40201-021-00655-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a signal’s time structure on the perceived noise annoyance of road traffic noise

Abstract: Purpose Road traffic noise is the most common source of noise in modern cities. The noise indicators used to manage noise do not take into account its temporal structure. However, in cities the traffic flow varies during the day, peaking due to congestion and more fluent periods. In this research we sought to analyze how people (giving answers on a numerical ICBEN scale) perceive noise stimuli with the same LAeqT values but different time structures (more/less noise events, different amplitude en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The problem of the number of noise events, expressed in IR, was also investigated by the author of this article in the preliminary study, limited only to three different sound level values and road traffic solely. The results showed that IR was not a statistically significant factor for the annoyance ratings (Felcyn, 2021). However, this problem needed further research, especially regarding also other types of noise sources.…”
Section: Introductionmentioning
confidence: 82%
“…The problem of the number of noise events, expressed in IR, was also investigated by the author of this article in the preliminary study, limited only to three different sound level values and road traffic solely. The results showed that IR was not a statistically significant factor for the annoyance ratings (Felcyn, 2021). However, this problem needed further research, especially regarding also other types of noise sources.…”
Section: Introductionmentioning
confidence: 82%